The Impact of Corporate Social Responsibility on Banking Financial Performance with Good Corporate Governance - Moch. Deni Rizal; Maria Rosa Kumala Dewi; Dhian Kristantiningtyas (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study was conducted to determine the effect of Corporate Social Responsibility (CSR) on Financial Performance with Good Corporate Governance (GCG) as a moderating variable in banking companies listed on the Indonesia Stock Exchange. The independent variable used in this study is CSR which is measured through 5 indicators including Dividend Payout Ratio, Staff Expenses Rate, Interest Payment Rate, Tax Proportion, and Proportion of Public Welfare Donation. The dependent variable used in this study is Financial Performance which is measured in 3 dimensions, namely the growth dimension with 4 indicators, profitability with 3 indicators, and risk management with 3 indicators. The moderating variable used in this study is GCG which is measured through the proportion of institutional ownership, managerial ownership, and foreign ownership. The population in this study are banking companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The type of research is quantitative testing. The sampling technique used is purposive sampling and 13 banking companies were obtained. This study uses PLS (Partial Least Square) analysis with the SmartPLS 3.0 application. Based on the results of the study, it shows that CSR has a significant positive effect on Financial Performance and GCG is unable to moderate the relationship between CSR and Financial Performance.